Visualized acid–base discoloration and optoelectronic investigations of azines and azomethines having double 4-[N, N-di(4-methoxyphenyl)amino]phenyl terminals1. Issue 29 (7th August 2015) - Ma, Bin-Bin; Zhang, Hua; Wang, Yu; Peng, Yu-Xin; Huang, Wei; Wang, Ming-Kui; Shen, Yan
<x xml:space="preserve">Abstract</x> MS-1 and MS-2 exhibit visualized acid–base discoloration, and MS-2 could be used as a low-cost HTM in perovskite solar cells.